JAVANESE CULTURAL VALUES THE DESIGN AND IMPLEMENTATION OF ACCOUNTING INFORMATION SYSTEMS IN MSMEs - Pinandita, Candra Pramula; Pratiwi, Berlina Yudha; Wijaya, Dwi Indriani Fidiastutik (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2025)
The Javanese community, which is the majority in Kediri, has unique and profound cultural values that have shaped their way of life, social interactions, and even business practices for generations. Values such as cooperation, empathy, harmony, and deliberation often serve as the foundation for interaction and business management. Based on the explanation above, the urgent research gap is the lack of in-depth understanding of how Javanese cultural values can be specifically and explicitly harmonized in the design and implementation process of accounting information systems in SMEs. This research aims to deeply explore how Javanese cultural values, firmly held MSMEs “Sambal Pecel Bu Siti Kediri”, influence and can be harmonized in the design and implementation of AIS. Javanese cultural values are an important foundation in the life of Javanese society, shaping worldviews, ethics, and daily behavior. This research is a qualitative study based on the philosophy of post-positivism, used to examine objects in their natural conditions. shows that the design and implementation of the AIS in the MSMEs